Cucurbit [n] uril modified composite chitosan material as well as preparation method and application thereof
By dispersing the cucurbita urea with chitosan and chitosan quaternary ammonium salts in solution and carrying out cross-linking reactions, a cucurbita modified composite chitosan material with high efficiency and good cycle stability was prepared, which solved the problem that existing adsorbents cannot have both adsorption efficiency and circulation performance.
Patent Information
- Application Number
- CN202510283077.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-06-27
AI Technical Summary
Existing anionic dye adsorbents cannot have good adsorption efficiency, circulation performance and recyclability.
The cucurbit [n]urea modified composite chitosan material was prepared by dispersing cucurbit [n]urea-modified composite chitosan material in solution and cross-linking reaction of glutaraldehyde and sodium tripolyphosphate. The material enhances adsorption stability through crosslinking reactions and forms a spherical structure that is easy to regenerate by secondary crosslinking.
It achieves efficient adsorption and good cycle stability of anionic dyes, and is also recyclable and suitable for treating wastewater containing a variety of anionic dyes.
Smart Images

Figure CN120209416A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and particularly relates to a cucurbit[n]uril modified composite chitosan material, a preparation method thereof, and an application thereof. Background Art
[0002] With the vigorous development of the printing and dyeing industry, the environmental pollution problems caused by dyes and heavy metal ions discharged in industrial wastewater have become increasingly prominent and have become urgent problems to be solved. The components of dye wastewater are complex, with high concentration, deep color, and are difficult to degrade, which has caused a very serious impact on environmental pollution. The commonly used methods for treating printing and dyeing wastewater are divided into three categories: physical methods, chemical methods, and biological methods. Among them, the adsorption method in physical methods is the most common method. Due to the limited adsorption capacity and poor regeneration performance of current adsorbents, developing efficient, economical, and renewable adsorbents is an important current research hotspot.
[0003] Cucurbit[n]uril is a cyclic compound prepared by the reaction of glycoluril and formaldehyde under acidic conditions. It has a pumpkin-like shape and a rigid cavity structure with completely symmetric external hydrophilic and internal hydrophobic properties. With the gradual in-depth research on cucurbit[n]uril, based on the separation of cucurbit[5]uril (CB[5]), cucurbit[6]uril (CB[6]), cucurbit[7]uril (CB[7]), and cucurbit[8]uril (CB[8]), cucurbit
[10] uril (CB
[10] ) has been further separated, expanding the cucurbit[n]uril family. Due to the pumpkin-like shape and the rigid cavity structure with completely symmetric external hydrophilic and internal hydrophobic properties of cucurbit[n]uril, it can achieve efficient adsorption of anionic dyes. However, the reusability of cucurbit[n]uril is poor, which to a certain extent restricts its application as an adsorbent. Finding an effective regeneration method to enable cucurbit[n]uril to be recycled will be the key to using cucurbit[n]uril as an adsorption material.
[0004] Chitosan, as the second most abundant polysaccharide in the world, contains abundant amino and hydroxyl groups, and has the advantages of wide source, low cost, non-toxicity, good biocompatibility, etc., and is widely used in adsorption. Chitosan is alkali-resistant but acid-sensitive, and has poor adsorption effect on high-concentration dyes, which limits its application as an adsorbent. Quaternized chitosan is a quaternized derivative of chitosan, which has good solubility, adsorption, flocculation, antibacterial activity, and biodegradability. In addition, due to the quaternary ammonium groups, amino groups, and hydrogen groups it possesses, quaternized chitosan has good adsorption ability for anionic dyes, but its inherent water solubility also brings difficulties to its recycling and utilization, restricting its practical application. Summary of the Invention
[0005] The object of the present invention is to overcome the problem that existing anion dye adsorbents cannot have both good adsorption efficiency, recycling performance and recyclability, and to provide a preparation method of a cucurbit[n]uril-modified composite chitosan material. The technological process of this method is simple, efficient, green and environmentally friendly. At the same time, the cucurbit[n]uril-modified composite chitosan material prepared by this method has both good adsorption efficiency, recycling performance and recyclability.
[0006] To achieve the above object, on the one hand, the present invention provides a preparation method of a cucurbit[n]uril-modified composite chitosan material, and this method includes the following steps:
[0007] (1) Disperse cucurbit[n]uril in a solution containing chitosan and chitosan quaternary ammonium salt to obtain a dispersion system;
[0008] (2) Conduct a primary cross-linking reaction on the dispersion system in step (1) with an aqueous glutaraldehyde solution;
[0009] (3) Conduct a secondary cross-linking reaction on the reactant obtained after the primary cross-linking reaction in step (2) with an aqueous sodium tripolyphosphate solution, then perform solid-liquid separation, and collect the solid-phase material for freeze-drying;
[0010] Among them, in step (1), the cucurbit[n]uril is at least one of cucurbit[5]uril, cucurbit[6]uril, cucurbit[7]uril and cucurbit[8]uril;
[0011] The weight ratio of the dosage of the chitosan to the chitosan quaternary ammonium salt is 1:0.1 - 0.8.
[0012] Preferably, in step (1), the weight ratio of the dosage of the chitosan to the chitosan quaternary ammonium salt is 1:0.5 - 0.7.
[0013] Preferably, in step (1), the ratio of the total dosage of the chitosan and the chitosan quaternary ammonium salt to the dosage of the cucurbit[n]uril is 1:0.2 - 0.7.
[0014] Preferably, in step (2), the conditions of the primary cross-linking reaction include: the temperature is 15 - 35°C, and the time is 0.5 - 2.5 h.
[0015] Preferably, the weight ratio of the chitosan to the volume of the aqueous glutaraldehyde solution is 100 g:10 - 70 mL.
[0016] Preferably, the mass concentration of the aqueous glutaraldehyde solution is 0.5 - 5%.
[0017] Preferably, in step (3), the conditions of the secondary cross-linking reaction include: the temperature is 40 - 60°C, and the time is 2 - 8 h.
[0018] Preferably, in step (3), the conditions for freeze-drying include: temperature of -70 to -50 °C and time of 14 to 24 h.
[0019] Preferably, the ratio of the total weight of the chitosan and the quaternary ammonium salt of chitosan to the volume of the aqueous sodium tripolyphosphate solution is 1 g: 180 to 400 mL.
[0020] Preferably, the mass concentration of the aqueous sodium tripolyphosphate solution is 0.5 to 5%.
[0021] In a second aspect of the present invention, there is provided a cucurbit[n]uril-modified composite chitosan material prepared by the above method.
[0022] In a third aspect of the present invention, there is provided the use of the above cucurbit[n]uril-modified composite chitosan material in treating sewage containing anionic dyes.
[0023] Preferably, the anionic dye is congo red and / or methyl orange.
[0024] Preferably, the anionic dye is congo red and methyl orange.
[0025] Preferably, in the sewage containing the anionic dye, the concentration of congo red is 50 to 1000 mg / L, and the concentration of methyl orange is 50 to 600 mg / L.
[0026] The cucurbit[n]uril-modified composite chitosan material (CB[n]-HACC-CS) obtained by the preparation method of the present invention has good adsorption performance for anionic dyes, has a high maximum adsorption capacity for a single anionic dye, and can also adsorb multiple anionic dyes simultaneously with a high equilibrium adsorption capacity for each anionic dye. In particular, it has a good treatment effect on sewage containing both congo red and methyl orange. At the same time, the cucurbit[n]uril-modified composite chitosan material can be recycled and has good adsorption stability. This is mainly because through a primary cross-linking reaction, chitosan (CS) and the quaternary ammonium salt of chitosan (HACC) are simultaneously cross-linked with glutaraldehyde to enhance its adsorption stability. At the same time, through a secondary cross-linking reaction, chitosan (CS) and the quaternary ammonium salt of chitosan (HACC) are cross-linked with sodium tripolyphosphate again to form a spherical material in which chitosan (CS) and the quaternary ammonium salt of chitosan (HACC) wrap powdered cucurbit[n]uril, making it easy to regenerate. Based on the compounding of chitosan (CS), the quaternary ammonium salt of chitosan (HACC) and cucurbit[n]uril and the quantitative relationship between chitosan (CS) and the quaternary ammonium salt of chitosan (HACC), through the primary cross-linking reaction of glutaraldehyde and the secondary cross-linking reaction of sodium tripolyphosphate, the cucurbit[n]uril-modified composite chitosan material has good adsorption performance, cyclic stability and recyclability for anionic dyes. Description of the Drawings
[0027] Figure 1 They are the infrared spectra of CB[6], CS, HACC, and CB[6]-HACC-CS in Example 1 of the present invention;
[0028] Figure 2 They are the physical pictures and scanning electron microscope pictures of the cucurbit[n]uril-modified composite chitosan material prepared in Example 1 of the present invention;
[0029] Figure 3 It is the Zeta potential diagram of the cucurbit[n]uril-modified composite chitosan material prepared in Example 1 of the present invention;
[0030] Figure 4 It is the isothermal adsorption curve diagram of the cucurbit[n]uril-modified composite chitosan material prepared in Example 1 of the present invention for anionic dyes;
[0031] Figure 5 It is the cycle performance diagram of the cucurbit[n]uril-modified composite chitosan material prepared in Example 1 of the present invention. Detailed Embodiments
[0032] The following provides a detailed description of the detailed embodiments of the present invention. It should be understood that the detailed embodiments described herein are only for explaining and illustrating the present invention, and are not used to limit the present invention.
[0033] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values and individual point values of each range, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.
[0034] The present invention provides a preparation method of a cucurbit[n]uril-modified composite chitosan material, and the method includes the following steps:
[0035] (1) Disperse cucurbit[n]uril in a solution containing chitosan and chitosan quaternary ammonium salt to obtain a dispersion system;
[0036] (2) Conduct a primary cross-linking reaction on the dispersion system in step (1) with an aqueous glutaraldehyde solution;
[0037] (3) Conduct a secondary cross-linking reaction on the reactant obtained after the primary cross-linking reaction in step (2) with an aqueous sodium tripolyphosphate solution, then perform solid-liquid separation, and collect the solid phase material for freeze-drying;
[0038] Among them, in step (1), the cucurbit[n]uril is at least one of cucurbit[5]uril, cucurbit[6]uril, cucurbit[7]uril, and cucurbit[8]uril;
[0039] The weight ratio of the dosage of the chitosan to that of the quaternary ammonium salt of chitosan is 1:0.1 - 0.8.
[0040] In a preferred embodiment, in order to further improve the adsorption performance and cycle stability of the cucurbit[n]uril-modified composite chitosan material, in step (1), the weight ratio of the dosage of the chitosan to that of the quaternary ammonium salt of chitosan is 1:0.5 - 0.7; specifically, the weight ratio of the dosage of the chitosan to that of the quaternary ammonium salt of chitosan can be 1:0.5, 1:0.55, 1:0.6, 1:0.65 or 1:0.7.
[0041] In the present invention, through step (1), cucurbit[n]uril is uniformly dispersed in a solution containing chitosan (CS) and quaternary ammonium salt of chitosan (HACC) to form a uniform and stable dispersion system; through the primary cross-linking reaction of glutaraldehyde in step (2), chitosan (CS) and quaternary ammonium salt of chitosan (HACC) in step (1) are simultaneously cross-linked with glutaraldehyde to enhance the strength and adsorption stability of the material; through the secondary cross-linking reaction of sodium tripolyphosphate in step (3), chitosan (CS) and quaternary ammonium salt of chitosan (HACC) are cross-linked with sodium tripolyphosphate again to form a spherical material in which powdered cucurbit[n]uril is wrapped by chitosan (CS) and quaternary ammonium salt of chitosan (HACC), making it easy to regenerate and improving its cycle stability. Finally, through freeze-drying, a spherical cucurbit[n]uril-modified composite chitosan material (CB[n]-HACC-CS) with a wrinkled structure on the surface is formed. This cucurbit[n]uril-modified composite chitosan material has good adsorption performance, cycle stability and recyclability for anionic dyes.
[0042] In the present invention, there is no special requirement for the solid-liquid separation method, and any conventional method in the art can be used, for example, it can be filtration.
[0043] In the present invention, in step (1), the cucurbit[n]uril is prepared by a conventional method in the art, and then cucurbit[5]uril (CB[5]), cucurbit[6]uril (CB[6]), cucurbit[7]uril (CB[7]) and cucurbit[8]uril (CB[8]) are obtained by separation through a brine separation method.
[0044] In the present invention, in step (1), the solution containing chitosan and quaternary ammonium salt of chitosan is obtained by mixing chitosan, quaternary ammonium salt of chitosan and an acidic solution. The acid in the acidic solution is selected from one or more of acetic acid, formic acid and hydrochloric acid; in the most preferred embodiment, the volume concentration of the acidic solution is 1 - 3%, and the acid in the acidic solution is acetic acid.
[0045] In the present invention, in step (1), there is no special requirement for the concentration of the solution containing chitosan and chitosan quaternary ammonium salt, as long as chitosan and chitosan quaternary ammonium salt can be completely dissolved.
[0046] In the present invention, the "chitosan quaternary ammonium salt" is "hydroxypropyltrimethylammonium chloride chitosan".
[0047] In a preferred embodiment, in order to improve the adsorption performance, cycle stability and recyclability of the cucurbit[n]uril modified composite chitosan material, in step (1), the ratio of the total amount of the chitosan and the chitosan quaternary ammonium salt to the amount of the cucurbit[n]uril is 1:0.2 - 0.7, preferably 1:0.2 - 0.5; specifically, the ratio of the total amount of the chitosan and the chitosan quaternary ammonium salt to the amount of the cucurbit[n]uril can be 1:0.2, 1:0.25, 1:0.3, 1:0.4, 1:0.45 or 1:0.5.
[0048] In a preferred embodiment, in step (2), the conditions for the first cross-linking reaction include: the temperature is 15 - 35°C and the time is 0.5 - 2.5 h.
[0049] In a specific embodiment, in step (2), an aqueous glutaraldehyde solution is added dropwise to the dispersion system in step (1) for the first cross-linking reaction.
[0050] In a preferred embodiment, in order to further improve the adsorption performance and cycle stability of the cucurbit[n]uril modified composite chitosan material, the ratio of the weight of the chitosan to the volume of the aqueous glutaraldehyde solution is 100 g:10 - 70 mL, preferably 100 g:13 - 67 mL.
[0051] In a preferred embodiment, in order to further improve the cycle stability of the cucurbit[n]uril modified composite chitosan material, the mass concentration of the aqueous glutaraldehyde solution is 0.5 - 5%, preferably 0.5 - 3%; specifically, the mass concentration of the aqueous glutaraldehyde solution can be 0.5%, 1%, 1.5%, 2%, 2.5% or 3%.
[0052] In a preferred embodiment, in step (3), the conditions for the second cross-linking reaction include: the temperature is 40 - 60°C and the time is 2 - 8 h.
[0053] In a specific embodiment, in step (3), the reactant obtained after the first cross-linking reaction in step (2) is added dropwise to an aqueous sodium tripolyphosphate solution for the second cross-linking reaction, preferably at a dropping rate of 1 - 5 seconds per drop.
[0054] In a preferred embodiment, to improve the cyclic stability and recyclability of the cucurbit[n]uril-modified composite chitosan material, the ratio of the total weight of the chitosan and the quaternary ammonium chitosan to the volume of the sodium tripolyphosphate aqueous solution is 1 g: 180-400 mL, preferably 1 g: 200-300 mL.
[0055] In a preferred embodiment, the mass concentration of the sodium tripolyphosphate aqueous solution is 0.5-5%, preferably 0.5-3%; specifically, the mass concentration of the sodium tripolyphosphate aqueous solution can be 0.5%, 1%, 1.5%, 2%, 2.5% or 3%.
[0056] In a preferred embodiment, to improve the adsorption performance of the cucurbit[n]uril-modified composite chitosan material, in step (3), the conditions for freeze-drying include: a temperature of -70 to -50 °C and a time of 14-24 h, preferably 14-18 h.
[0057] In a preferred embodiment, step (3) further includes a process of washing the collected solid-phase material before freeze-drying; specifically, deionized water is used to wash the intermediate product to neutrality.
[0058] The present invention also provides a cucurbit[n]uril-modified composite chitosan material prepared by the above method.
[0059] The cucurbit[n]uril-modified composite chitosan material prepared by the above method has a rich specific surface area. At the same time, due to the rigid cavity structure of cucurbit[n]uril and the cations introduced by the quaternary ammonium chitosan, it has good adsorption performance for anionic dyes. At the same time, since the cucurbit[n]uril-modified composite chitosan material has a spherical structure with good strength, it also has good cyclic stability and recyclability.
[0060] The present invention also provides an application of the above cucurbit[n]uril-modified composite chitosan material in treating sewage containing anionic dyes.
[0061] The cucurbit[n]uril-modified composite chitosan material described in the present invention not only has good adsorption performance for sewage containing only anionic dyes, but also has good adsorption performance for sewage containing multiple anionic dyes, and its final equilibrium adsorption capacity is high.
[0062] In a preferred embodiment, the anionic dye is congo red and / or methyl orange.
[0063] In a more preferred embodiment, the anionic dye is congo red and methyl orange.
[0064] In a preferred embodiment, in the sewage of the anionic dye, the concentration of Congo red is 50-1000 mg / L, and the concentration of methyl orange is 50-600 mg / L.
[0065] The following examples further illustrate a cucurbit[n]uril-modified composite chitosan material, its preparation method and application according to the present invention. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation manners and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0066] In the following examples, the experimental methods, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, can all be obtained commercially.
[0067] Example 1
[0068] (1) 0.5 g of cucurbit[6]uril was dispersed in a solution containing chitosan and chitosan quaternary ammonium salt, and a dispersion system was obtained by mechanical stirring. Among them, the solution containing chitosan and chitosan quaternary ammonium salt was obtained by ultrasonic mixing of 0.75 g of chitosan, 0.5 g of hydroxypropyl trimethyl ammonium chloride chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0069] (2) 0.2 mL of an aqueous solution of glutaraldehyde with a mass concentration of 1% was added dropwise to the dispersion system in step (1), and stirred at 25 °C for 1 h for a primary cross-linking reaction;
[0070] (3) The reactant obtained after the primary cross-linking reaction in step (2) was added dropwise to 300 mL of an aqueous solution of sodium tripolyphosphate with a mass concentration of 1%, stirred at 50 °C for 8 h for a secondary cross-linking reaction, and then solid-liquid separation was carried out. The solid phase material was collected, washed with deionized water to neutral, and then freeze-dried at -70 °C for 14 h to obtain (CB[6]-HACC-CS)F1.
[0071] Example 2
[0072] (1) 0.35 g of cucurbit[5]uril was dispersed in a solution containing chitosan and chitosan quaternary ammonium salt, and a dispersion system was obtained by mechanical stirring. Among them, the solution containing chitosan and chitosan quaternary ammonium salt was obtained by ultrasonic mixing of 0.75 g of chitosan, 0.5 g of hydroxypropyl trimethyl ammonium chloride chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0073] (2) 0.2 mL of an aqueous solution of glutaraldehyde with a mass concentration of 3% was added dropwise to the dispersion system in step (1), and stirred at 25 °C for 1 h for a primary cross-linking reaction;
[0074] (3) The reactant obtained after the first cross-linking reaction in step (2) was dropped into 300 mL of an aqueous solution of sodium tripolyphosphate with a mass concentration of 3%, and stirred at 50 °C for 8 h for the second cross-linking reaction. Then, solid-liquid separation was carried out, and the solid phase material was collected and washed with deionized water until neutral, and then freeze-dried at -50 °C for 14 h to obtain (CB[5]-HACC-CS)F2.
[0075] Example 3
[0076] (1) 0.45 g of cucurbit[6]uril was dispersed in a solution containing chitosan and quaternary ammonium chitosan, and a dispersion system was obtained by mechanical stirring. Among them, the solution containing chitosan and quaternary ammonium chitosan was obtained by ultrasonic mixing of 0.75 g of chitosan, 0.375 g of hydroxypropyltrimethylammonium chloride chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0077] (2) 0.2 mL of an aqueous solution of glutaraldehyde with a mass concentration of 1% was dropped into the dispersion system in step (1), and stirred at 25 °C for 1 h for the first cross-linking reaction;
[0078] (3) The reactant obtained after the first cross-linking reaction in step (2) was dropped into 300 mL of an aqueous solution of sodium tripolyphosphate with a mass concentration of 1%, and stirred at 50 °C for 8 h for the second cross-linking reaction. Then, solid-liquid separation was carried out, and the solid phase material was collected and washed with deionized water until neutral, and then freeze-dried at -70 °C for 14 h to obtain (CB[6]-HACC-CS)F3.
[0079] Example 4
[0080] (1) 0.54 g of cucurbit[6]uril was dispersed in a solution containing chitosan and quaternary ammonium chitosan, and a dispersion system was obtained by mechanical stirring. Among them, the solution containing chitosan and quaternary ammonium chitosan was obtained by ultrasonic mixing of 0.75 g of chitosan, 0.6 g of hydroxypropyltrimethylammonium chloride chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0081] (2) 0.2 mL of an aqueous solution of glutaraldehyde with a mass concentration of 1% was dropped into the dispersion system in step (1), and stirred at 25 °C for 1 h for the first cross-linking reaction;
[0082] (3) The reactant obtained after the first cross-linking reaction in step (2) was dropped into 300 mL of an aqueous solution of sodium tripolyphosphate with a mass concentration of 1%, and stirred at 50 °C for 8 h for the second cross-linking reaction. Then, solid-liquid separation was carried out, and the solid phase material was collected and washed with deionized water until neutral, and then freeze-dried at -70 °C for 14 h to obtain (CB[6]-HACC-CS)F4.
[0083] Example 5
[0084] (1)Disperse 0.4 g of cucurbit[6]uril in a solution containing chitosan and quaternary ammonium chitosan salt, and obtain a dispersion system through mechanical stirring. Among them, the solution containing chitosan and quaternary ammonium chitosan salt is obtained by ultrasonic mixing of 0.75 g of chitosan, 0.25 g of hydroxypropyltrimethylammonium chloride chitosan, and 30 mL of acetic acid solution with a volume concentration of 1%;
[0085] (2)Drop 0.2 mL of aqueous glutaraldehyde solution with a mass concentration of 1% into the dispersion system in step (1), and carry out a primary cross-linking reaction by stirring at 25 °C for 1 h;
[0086] (3)Drop the reactant obtained after the primary cross-linking reaction in step (2) into 300 mL of aqueous sodium tripolyphosphate solution with a mass concentration of 1%, stir at 50 °C for 8 h to carry out a secondary cross-linking reaction, then carry out solid-liquid separation, collect the solid phase material, wash it with deionized water until neutral, and then freeze-dry it at -70 °C for 14 h to obtain (CB[6]-HACC-CS)F5.
[0087] Example 6
[0088] (1)Disperse 1 g of cucurbit[6]uril in a solution containing chitosan and quaternary ammonium chitosan salt, and obtain a dispersion system through mechanical stirring. Among them, the solution containing chitosan and quaternary ammonium chitosan salt is obtained by ultrasonic mixing of 0.75 g of chitosan, 0.5 g of hydroxypropyltrimethylammonium chloride chitosan, and 30 mL of acetic acid solution with a volume concentration of 1%;
[0089] (2)Drop 0.2 mL of aqueous glutaraldehyde solution with a mass concentration of 1% into the dispersion system in step (1), and carry out a primary cross-linking reaction by stirring at 25 °C for 1 h;
[0090] (3)Drop the reactant obtained after the primary cross-linking reaction in step (2) into 300 mL of aqueous sodium tripolyphosphate solution with a mass concentration of 1%, stir at 50 °C for 8 h to carry out a secondary cross-linking reaction, then carry out solid-liquid separation, collect the solid phase material, wash it with deionized water until neutral, and then freeze-dry it at -70 °C for 14 h to obtain (CB[n]-HACC-CS)F6.
[0091] Comparative Example 1
[0092] Carry out the implementation in the manner of Example 1, the difference is that in step (1), hydroxypropyltrimethylammonium chloride chitosan is not added, that is:
[0093] (1)Disperse 0.5 g of cucurbit[6]uril in a chitosan solution, and obtain a dispersion system through mechanical stirring. Among them, the chitosan solution is obtained by ultrasonic mixing of 0.75 g of chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0094] (2) Add 0.2 mL of a 1% glutaraldehyde aqueous solution by mass to the dispersion system in step (1), and carry out a primary cross-linking reaction by stirring at 25 °C for 1 h;
[0095] (3) Add the reactant obtained after the primary cross-linking reaction in step (2) to 300 mL of a 1% sodium tripolyphosphate aqueous solution, stir at 50 °C for 8 h to carry out a secondary cross-linking reaction, then carry out solid-liquid separation, collect the solid phase material, wash it with deionized water until neutral, and then freeze-dry it at -70 °C for 14 h to obtain (CB[6]-CS)D1.
[0096] Comparative Example 2
[0097] Implement in the same manner as in Example 1, the difference is that in step (1), cucurbit[6]uril is not added, that is:
[0098] (1) Ultrasonically mix 0.75 g of chitosan, 0.5 g of hydroxypropyltrimethylammonium chloride chitosan, and 30 mL of a 1% acetic acid solution by volume to obtain a solution containing chitosan and chitosan quaternary ammonium salt;
[0099] (2) Add 0.2 mL of a 1% glutaraldehyde aqueous solution by mass to the solution containing chitosan and chitosan quaternary ammonium salt in step (1), and carry out a primary cross-linking reaction by stirring at 25 °C for 1 h;
[0100] (3) Add the reactant obtained after the primary cross-linking reaction in step (2) to 300 mL of a 1% sodium tripolyphosphate aqueous solution, stir at 50 °C for 8 h to carry out a secondary cross-linking reaction, then carry out solid-liquid separation, collect the solid phase material, wash it with deionized water until neutral, and then freeze-dry it at -70 °C for 14 h to obtain (HACC-CS)D2.
[0101] Comparative Example 3
[0102] Implement in the same manner as in Example 1, the difference is that in step (1), chitosan is not added, that is:
[0103] (1) Disperse 0.5 g of cucurbit[6]uril in a chitosan quaternary ammonium salt solution, and obtain a dispersion system by mechanical stirring, wherein the chitosan quaternary ammonium salt solution is obtained by ultrasonically mixing 0.5 g of hydroxypropyltrimethylammonium chloride chitosan and 30 mL of a 1% acetic acid solution by volume;
[0104] (2) Add 0.2 mL of a 1% glutaraldehyde aqueous solution by mass to the dispersion system in step (1), and carry out a primary cross-linking reaction by stirring at 25 °C for 1 h;
[0105] (3) The reactant obtained after the first cross-linking reaction in step (2) was dropped into 300 mL of an aqueous solution of sodium tripolyphosphate with a mass concentration of 1% and stirred at 50 °C for 8 h for the second cross-linking reaction. Then, solid-liquid separation was carried out, and the solid phase material was collected and washed with deionized water until neutral, and then freeze-dried at -70 °C for 14 h to obtain (CB[6]-HACC)D3.
[0106] Comparative Example 4
[0107] It was carried out in the same manner as in Example 1, except that step (2) was not carried out, that is:
[0108] (1) 0.5 g of cucurbit[6]uril was dispersed in a solution containing chitosan and chitosan quaternary ammonium salt, and a dispersion system was obtained by mechanical stirring. Among them, the solution containing chitosan and chitosan quaternary ammonium salt was obtained by ultrasonic mixing of 0.75 g of chitosan, 0.5 g of hydroxypropyltrimethylammonium chloride chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0109] (2) The dispersion system in step (1) was dropped into 300 mL of an aqueous solution of sodium tripolyphosphate with a mass concentration of 1% and stirred at 50 °C for 8 h for the second cross-linking reaction. Then, solid-liquid separation was carried out, and the solid phase material was collected and washed with deionized water until neutral, and then freeze-dried at -70 °C for 14 h to obtain (CB[6]-HACC-CS)D4.
[0110] Comparative Example 5
[0111] It was carried out in the same manner as in Example 1, except that step (3) was not carried out, that is:
[0112] (1) 0.5 g of cucurbit[6]uril was dispersed in a solution containing chitosan and chitosan quaternary ammonium salt, and a dispersion system was obtained by mechanical stirring. Among them, the solution containing chitosan and chitosan quaternary ammonium salt was obtained by ultrasonic mixing of 0.75 g of chitosan, 0.5 g of hydroxypropyltrimethylammonium chloride chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0113] (2) 0.2 mL of an aqueous solution of glutaraldehyde with a mass concentration of 1% was dropped into the dispersion system in step (1), and stirred at 25 °C for 1 h for the first cross-linking reaction to obtain (CB[6]-HACC-CS)D5.
[0114] Comparative Example 6
[0115] It was carried out in the same manner as in Example 2, except that in step (1), hydroxypropyltrimethylammonium chloride chitosan was not added, that is:
[0116] (1) Disperse 0.35 g of cucurbit[5]uril in a solution containing chitosan, and obtain a dispersion system through mechanical stirring. Among them, the solution containing chitosan is obtained by ultrasonic mixing of 0.75 g of chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0117] (2) Drop 0.2 mL of aqueous glutaraldehyde solution with a mass concentration of 3% into the dispersion system in step (1), and carry out a primary cross-linking reaction by stirring at 25 °C for 1 h;
[0118] (3) Drop the reactant obtained after the primary cross-linking reaction in step (2) into 300 mL of aqueous sodium tripolyphosphate solution with a mass concentration of 3%, stir at 50 °C for 8 h to carry out a secondary cross-linking reaction, then carry out solid-liquid separation, collect the solid phase material, wash it with deionized water until neutral, and then freeze-dry it at -50 °C for 14 h to obtain (CB[5]-CS)D6.
[0119] Comparative Example 7
[0120] Carry out the implementation in the manner of Example 2. The difference is that in step (1), cucurbit[5]uril is not added, that is:
[0121] (1) Obtain a solution containing chitosan and chitosan quaternary ammonium salt by ultrasonic mixing of 0.75 g of chitosan, 0.5 g of hydroxypropyltrimethylammonium chloride chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0122] (2) Drop 0.2 mL of aqueous glutaraldehyde solution with a mass concentration of 3% into the solution containing chitosan and chitosan quaternary ammonium salt in step (1), and carry out a primary cross-linking reaction by stirring at 25 °C for 1 h;
[0123] (3) Drop the reactant obtained after the primary cross-linking reaction in step (2) into 300 mL of aqueous sodium tripolyphosphate solution with a mass concentration of 3%, stir at 50 °C for 8 h to carry out a secondary cross-linking reaction, then carry out solid-liquid separation, collect the solid phase material, wash it with deionized water until neutral, and then freeze-dry it at -50 °C for 14 h to obtain (HACC-CS)D7.
[0124] Comparative Example 8
[0125] Carry out the implementation in the manner of Example 2. The difference is that in step (1), chitosan is not added, that is:
[0126] (1) Disperse 0.35 g of cucurbit[5]uril in a solution containing chitosan quaternary ammonium salt, and obtain a dispersion system through mechanical stirring. Among them, the solution containing chitosan quaternary ammonium salt is obtained by ultrasonic mixing of 0.5 g of hydroxypropyltrimethylammonium chloride chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0127] (2) Add 0.2 mL of an aqueous glutaraldehyde solution with a mass concentration of 3% dropwise to the dispersion system in step (1), and carry out a primary cross-linking reaction by stirring at 25 °C for 1 h;
[0128] (3) Drop the reactant obtained after the primary cross-linking reaction in step (2) into 300 mL of an aqueous sodium tripolyphosphate solution with a mass concentration of 3%, stir at 50 °C for 8 h to carry out a secondary cross-linking reaction, then carry out solid-liquid separation, collect the solid phase material, wash it with deionized water until neutral, and then freeze-dry it at -50 °C for 14 h to obtain (CB[5]-HACC)D8.
[0129] Comparative Example 9
[0130] Carry out the implementation in the same way as in Example 2, the difference is that step (2) is not carried out, that is:
[0131] (1) Disperse 0.35 g of cucurbit[5]uril in a solution containing chitosan and quaternary ammonium salt of chitosan, and obtain a dispersion system by mechanical stirring. Among them, the solution containing chitosan and quaternary ammonium salt of chitosan is obtained by ultrasonic mixing of 0.75 g of chitosan, 0.5 g of hydroxypropyltrimethylammonium chloride chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0132] (2) Drop the dispersion system in step (1) into 300 mL of an aqueous sodium tripolyphosphate solution with a mass concentration of 3%, stir at 50 °C for 8 h to carry out a secondary cross-linking reaction, then carry out solid-liquid separation, collect the solid phase material, wash it with deionized water until neutral, and then freeze-dry it at -50 °C for 14 h to obtain (CB[5]-HACC-CS)D9.
[0133] Comparative Example 10
[0134] Carry out the implementation in the same way as in Example 2, the difference is that step (3) is not carried out, that is:
[0135] (1) Disperse 0.35 g of cucurbit[5]uril in a solution containing chitosan and quaternary ammonium salt of chitosan, and obtain a dispersion system by mechanical stirring. Among them, the solution containing chitosan and quaternary ammonium salt of chitosan is obtained by ultrasonic mixing of 0.75 g of chitosan, 0.5 g of hydroxypropyltrimethylammonium chloride chitosan and 30 mL of acetic acid solution with a volume concentration of 1%;
[0136] (2) Add 0.2 mL of an aqueous glutaraldehyde solution with a mass concentration of 3% dropwise to the dispersion system in step (1), and carry out a primary cross-linking reaction by stirring at 25 °C for 1 h to obtain (CB[5]-HACC-CS)D10.
[0137] Test Example
[0138] (1) The Fourier transform infrared spectrometer was used to perform infrared characterization on CB[6], CS, HACC, and CB[6]-HACC-CS in Example 1, and the results are as Figure 1 shown;
[0139] It can be seen from Figure 1 that: in the infrared band of CB[6]-HACC-CSF1, the main infrared characteristic signals of chitosan, chitosan quaternary ammonium salt, and cucurbit[6]uril are all presented. 1723 cm -1 is the stretching vibration of the carbonyl group on CB[6]; chitosan has a -NH characteristic bending vibration absorption peak at 1598 cm -1 . In the infrared spectrum of chitosan quaternary ammonium salt, the -NH characteristic bending vibration absorption peak at 1598 cm -1 is significantly weakened. At the same time, a strong absorption peak of the C-H bending vibration of -CH3 of the quaternary ammonium group appears at 1485 cm -1 . This indicates that chitosan quaternary ammonium salt is obtained by grafting quaternary ammonium groups onto the amino group of chitosan. At the same time, a strong absorption peak of the C-H bending vibration of -CH3 of the quaternary ammonium group also appears near 1485 cm -1 in the infrared spectrum of CB[6]-HACC-CSF1, which shows that the loading of chitosan quaternary ammonium salt is completed. A characteristic absorption peak of the C=N structure appears at 1566 cm -1 , indicating that the aldehyde group of the cross-linking agent glutaraldehyde mainly reacts with the amino group to form a C=N (Schiff base) structure.
[0140] (2) The physical object of CB[6]-HACC-CSF1 prepared in Example 1 was photographed, and at the same time, the scanning electron microscope was used to perform microscopic morphology characterization on CB[6]-HACC-CSF1 prepared in Example 1. The results are as Figure 2 shown, where Figure 2 (a) is a physical picture of CB[6]-HACC-CSF1 prepared in Example 1; Figure 2 (b) is a surface electron microscope picture of CB[6]-HACC-CSF1 prepared in Example 1 magnified 2000 times; Figure 2 (c) is a cross-section electron microscope picture of CB[6]-HACC-CSF1 prepared in Example 1 magnified 2500 times; Figure 2 (d) is a cross-section electron microscope picture of CB[6]-HACC-CSF1 prepared in Example 1 magnified 3000 times;
[0141] It can be seen from Figure 2 (a) that: CB[6]-HACC-CS prepared by the method described in the present invention presents a regular spherical shape with a relatively large diameter, and this spherical structure is beneficial for subsequent recycling and regeneration;
[0142] It can be seen from Figure 2(b) It can be seen that the surface of CB[6]-HACC-CS prepared by the method of the present invention is rough and loose with wrinkled shape, indicating that it has a large specific surface area;
[0143] It can be seen from Figure 2 (c) and 2(d) that there are abundant pore structures distributed inside CB[6]-HACC-CS prepared by the method of the present invention. This three-dimensional network structure provides more adsorption active sites for the adsorption of anionic dyes.
[0144] (3) Zeta potential test was used to characterize CB[6]-HACC-CSF1 prepared in Example 1, and the results are as Figure 3 shown;
[0145] It can be seen from Figure 3 that the zeta potential of CB[6]-HACC-CSF1 is higher than 0 mV in the whole pH range. Thus, it can be known that in the present invention, positively charged CB[6]-HACC-CSF1 adsorbs anionic dyes through electrostatic interaction, so as to achieve the purpose of removing anionic dyes in sewage. The higher the positive charge carried on the surface of CB[6]-HACC-CSF1, the more beneficial it is to the adsorption of anionic dyes.
[0146] (4) The anionic dye adsorption performance of CB[6]-HACC-CSF1 prepared in Example 1 was tested, and the results are as Figure 4 shown;
[0147] It can be seen from Figure 4 that the Sips isotherm model can well describe the adsorption equilibrium data of CB[6]-HACC-CSF1 for congo red and methyl orange. Its adsorption model belongs to the Sips isotherm model. The Sips isotherm model belongs to the mixed model of Langmuir and Freundlich. The R 2 of the Sips isotherm model is higher than that of Langmuir and Freundlich. Among them, the maximum equilibrium adsorption amounts of CB[6]-HACC-CSF1 for congo red and methyl orange obtained by Sips fitting are 1559.7 mg / g and 315.2 mg / g respectively. Thus, it can be seen that CB[6]-HACC-CSF1 has a high maximum equilibrium adsorption amount for anionic dyes.
[0148] (5) The cycle stability of CB[6]-HACC-CSF1 prepared in Example 1 was tested. CB[6]-HACC-CSF1 prepared in Example 1 was used to adsorb 50 mL of simulated wastewater with a congo red concentration of 100 mg / L. After 10 h of adsorption, a 10% sodium chloride methanol solution was used as the eluent, and the concentration of the congo red dye solution was tested with a UV spectrophotometer. Such a cycle was carried out 5 times, and its cycle removal rate is asFigure 5 as shown
[0149] It can be seen from Figure 5 that in the five cycles, the adsorption capacity of CB[6]-HACC-CSB for congo red gradually decreases. This may be due to certain losses during the repeated use of the composite aerogel beads. However, after 5 adsorption-desorption cycle experiments, the final removal rate of CB[6]-HACC-CSB for congo red is still as high as 66.3%. It can be seen that the CB[6]-HACC-CS described in the present invention can not only be recycled but also has good cycle stability.
[0150] (6) Test the adsorption performance of the samples prepared in the examples and comparative examples. The test method is as follows: Add the samples to the simulated wastewater containing the same concentration of anionic dye solution respectively. After adsorption for 10 h, take the supernatant, measure the absorbance of the dye solution with a UV spectrophotometer, and then calculate the removal rate and adsorption capacity according to formulas (1) and (2) respectively;
[0151] Removal rate = (C0 - C e ) / C0 * 100% (1)
[0152] Adsorption capacity = (C0 - C e ) * V / m (2)
[0153] Among them: in formulas (1) and (2), C0 is the initial concentration of the solution, C e is the equilibrium concentration of the solution, and the units are both mg / L; m is the mass of the sample, and the unit is mg; V is the volume of the simulated wastewater, and the unit is L; the mass of the sample used is 10 mg, and the volume of the simulated wastewater is 50 mL; the concentrations of congo red and methyl orange in the simulated wastewater are both 100 mg / L. The calculation results are shown in Table 1;
[0154] Table 1
[0155]
[0156] "-" indicates that the test cannot be carried out due to the non-forming of the material
[0157] As can be seen from the results in Table 1, when the cucurbit[n]uril-modified composite chitosan material prepared by the method of the present invention is used to treat sewage containing both Congo red and methyl orange as two anionic dyes, these two anionic dyes can be adsorbed simultaneously. When cucurbit[n]uril is cucurbit[6]uril, the cucurbit[n]uril-modified composite chitosan material of the present invention has a removal effect on both Congo red and methyl orange. The removal rate of Congo red is as high as 92.7%, and the removal rate of methyl orange reaches 30.5%. For sewage with an initial concentration of 100 mg / L of Congo red and methyl orange, the adsorption amount of Congo red is 350 mg / g or more, and the adsorption amount of methyl orange is 100 mg / g or more. Among them, although the adsorption amount and removal rate of the material prepared in Comparative Example 4 are similar to those of the cucurbit[6]uril-modified composite chitosan material prepared by the method of the present invention, this material is extremely easy to break and is not easy to recycle and reuse; when cucurbit[n]uril is cucurbit[5]uril, the cucurbit[n]uril-modified composite chitosan material of the present invention has a removal effect on both Congo red and methyl orange. The removal rate of Congo red is as high as 74.9%, and the removal rate of methyl orange reaches 24.2%. For sewage with an initial concentration of 100 mg / L of Congo red and methyl orange, the adsorption amount of Congo red is about 370 mg / g, and the adsorption amount of methyl orange is about 120 mg / g. Among them, although the adsorption amount and removal rate of the material prepared in Comparative Example 9 are similar to those of the cucurbit[5]uril-modified composite chitosan material prepared by the method of the present invention, this material is extremely easy to break and is not easy to recycle and reuse.
[0158] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.
Claims
1. A method for preparing a cucurbit [n] uril modified composite chitosan material, characterized in that: The method comprises the following steps: (1) dispersing cucurbitac[n]uril in a solution containing chitosan and chitosan quaternary ammonium salt to obtain a dispersed system; (2) subjecting the dispersed system of step (1) to a primary cross-linking reaction with an aqueous solution of glutaraldehyde; (3) subjecting the reactant obtained after the primary cross-linking reaction in step (2) to a secondary cross-linking reaction with an aqueous solution of sodium tripolyphosphate, and then performing solid-liquid separation, collecting the solid phase material and performing freeze-drying; Wherein, in step (1), the cucurbit[n]uril is at least one of cucurbit[5]uril, cucurbit[6]uril, cucurbit[7]uril and cucurbit[8]uril; The weight ratio of the chitosan to the chitosan quaternary ammonium salt is 1:0.1-0.
8.
2. The method according to claim 1, characterized in that In step (1), the weight ratio of the chitosan to the chitosan quaternary ammonium salt is 1:0.5-0.
7.
3. The method according to claim 1 or 2, characterized in that: In step (1), the ratio of the total amount of the chitosan and the chitosan quaternary ammonium salt to the amount of the cucurbit[n]uril is 1:0.2-0.
7.
4. The method according to claim 3, characterized in that In step (2), the conditions of the primary cross-linking reaction include: temperature of 15 to 35° C. and time of 0.5 to 2.5 h.
5. The method according to claim 1 or 4, characterized in that: The ratio of the weight of the chitosan to the volume of the glutaraldehyde aqueous solution is 100 g: 10-70 mL; Preferably, the mass concentration of the glutaraldehyde aqueous solution is 0.5-5%.
6. The method according to claim 5, characterized in that In step (3), the conditions of the secondary cross-linking reaction include: a temperature of 40 to 60° C. and a time of 2 to 8 hours; and / or The freeze-drying conditions include: temperature of -70 to -50°C and time of 14 to 24 hours.
7. The method according to claim 1 or 6, characterized in that: The ratio of the total weight of the chitosan and the chitosan quaternary ammonium salt to the volume of the sodium tripolyphosphate aqueous solution is 1 g: 180-400 mL; Preferably, the mass concentration of the sodium tripolyphosphate aqueous solution is 0.5-5%.
8. Cucurbitac[n]uril modified composite chitosan material prepared by the method according to any one of claims 1 to 7.
9. Use of the cucurbitac[n]uril modified composite chitosan material according to claim 8 in treating wastewater containing anionic dyes.
10. The use according to claim 9, characterized in that: The anionic dye is Congo red and / or methyl orange; Preferably, the anionic dyes are Congo red and methyl orange; Preferably, in the wastewater containing anionic dyes, the concentration of Congo red is 50 to 1000 mg / L, and the concentration of methyl orange is 50 to 600 mg / L.